Phenotypic evaluation of F10 soybean generations from Grobogan x Slamet cross for large seed size selection - Hidayat, Ponendi; Nurtiati, Nurtiati; Ulinnuha, Zulfa; Adellansyah, Adellansyah (Kultivasi, 2025)
Soybeans are an important crop with high nutritional value and diverse uses. Current consumer and industry preference is for soybean varieties with large seeds and high productivity. To meet these demands, one effective approach is through hybridization. This study aims to evaluate the phenotype of F10 soybean line from a cross between Grobogan and Slamet for large-seeded and high-yield. The study was conducted in the screenhouse and Plant Breeding and Biotechnology Laboratory, Faculty of Agriculture, Jenderal Soedirman University. The experiment used a Randomized Complete Block Design (RCBD) with three replications, testing genotypes from Slamet x Grobogan crosses and three check varieties: Slamet, Grobogan, and Wilis. Observational data were analyzed using analysis of variance (ANOVA) with a 5% error rate and continued with LSD to select lines with high-performing genotype. The results of the ANOVA showed that the tested lines affected growth parameters and plant yield components. LSD analysis showed that the highest leaf length and number of leaves were in GS 7. In seed weight per plant, all lines were below Grobogan, followed by GS 7 and GS 47. In 100 seed weight, all lines were below Grobogan, but there were lines with large seed categories (> 14 g/100 seeds), namely GS7, GS 12, GS 36, and GS 39. Correlation analysis showed that the number of pods and 100 seed weight were positively correlated with seed weight per plant. Therefore, these traits can be selection indicators to identify high-yielding soybean genotype.